1995
DOI: 10.1111/j.1476-5381.1995.tb15115.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐chlorophenylpiperazine attenuates formalin‐induced nociceptive responses through 5‐HT1/2 receptors in both normal and diabetic mice

Abstract: 1 This study was designed to investigate the effect of meta-chlorophenylpiperazine (m-CPP; a 5-hydroxytryptamine (5-HT) receptor agonist) on the formalin-induced nociceptive responses in normal, insulin-dependent streptozotocin (STZ) diabetic and non-insulin dependent genetically diabetic (db/db) mice.2 A subcutaneous injection of diluted formalin (1% formaldehyde in 0.9% saline, 10 yl) under the plantar surface of the left hindpaw induced biphasic nociceptive responses, the first and second phases considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, the effect of endogenous opioids may be also correlated with serotonin release from the spinal cord in diabetic rats (14). Recent studies have provided evidence that the pain occurring in diabetic neuropathy can be attenuated by indirect activation of central 5-HT 1 and 5-HT 2 receptors (15), and that 5-hydroxytryptaminergic antinociceptive pathways are barely affected by diabetes (16).…”
mentioning
confidence: 99%
“…However, the effect of endogenous opioids may be also correlated with serotonin release from the spinal cord in diabetic rats (14). Recent studies have provided evidence that the pain occurring in diabetic neuropathy can be attenuated by indirect activation of central 5-HT 1 and 5-HT 2 receptors (15), and that 5-hydroxytryptaminergic antinociceptive pathways are barely affected by diabetes (16).…”
mentioning
confidence: 99%
“…Similar behaviour was observed for the 5-hydroxytryptamine re-uptake inhibitor trazodone, which also potentiated analgesia in conjunction with 5hydroxytryptophan. Trazodone might form 3chlorophenylpiperazine during its biotransformation in-vivo (Caccia & Garattini 1990) and 5hydroxytryptaminergic activity of arylpiperazinyl groups has been established (Fuller et a1 1978;Maj et a1 1979;Kahn & Wetzler 1991;Fontaine 1993;Takeshita & Yamaguchi 1995). These results provide support for the hypothesis that the antinociceptive action of 3 and 4 is partly a central event mediated through 5-hydroxytryptamine.…”
Section: Pharmacological Studiesmentioning
confidence: 77%
“…Recent experimental evidence has suggested that insulin has analgesic effects by acting on dopaminergic, and serotonergic analgesic pathways, among others (Anuradha et al., 2004; Dehkordi et al., 2017; Takeshita & Yamaguchi, 1997). In this study, ICV insulin injection produced an analgesic effect in rats.…”
Section: Discussionmentioning
confidence: 99%